2012
DOI: 10.1590/s2176-94512012000100016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the dental arch asymmetry in natural normal occlusion and Class II malocclusion individuals

Abstract: OBJECTIVE: To verify the presence and degree of asymmetry of dental arches in Brazilian individuals with natural normal occlusion and Class II, Divisions 1 and 2 malocclusions. METHODS: The study evaluated the symmetry of the maxillary and mandibular dental arches of 180 pairs of dental casts, divided into: Group I = 60 pairs of natural normal occlusion individuals; Group II = 60 pairs of Class II, Division 1 malocclusion individuals; and Group III = 60 pairs of Class II, Division 2 malocclusion individuals. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
1
11
0
1
Order By: Relevance
“…(14) A study by Scanavini et al in Brazil in 2012 revealed that asymmetrical values were observed in the dental arches of individuals with normal occlusion and Class II and Class III malocclusions. (15) The level of asymmetry in the mandibular arch was greater than that in the maxillary arch, but in our study, symmetrical values were evaluated regarding the teeth size ratios. In 2011, Malkoç et al in Turkey discovered that there was a significant difference in the mesiodistal dimensions of the teeth between males and females.…”
Section: Resultsmentioning
confidence: 84%
“…(14) A study by Scanavini et al in Brazil in 2012 revealed that asymmetrical values were observed in the dental arches of individuals with normal occlusion and Class II and Class III malocclusions. (15) The level of asymmetry in the mandibular arch was greater than that in the maxillary arch, but in our study, symmetrical values were evaluated regarding the teeth size ratios. In 2011, Malkoç et al in Turkey discovered that there was a significant difference in the mesiodistal dimensions of the teeth between males and females.…”
Section: Resultsmentioning
confidence: 84%
“…Distance of canines (DC) is the linear measurement from right to left canine tips ( Figure 3). This angular and linear measurement of upper and lower arch dental asymmetry has predictive accuracy and is marked as negative if shifted to the left (Scanavini et al, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…In some emerging countries, panoramic radiographs were suitable for screening CH, although the diagnostic gold standard was to assess condylar growth activity using bone scintigraphy (Nolte et al, 2015). Previous studies have also reported that there were no significant association between vertical mandibular asymmetry and temporomandibular disorder symptom (Mendoza-García et al, 2019;Sofyanti et al, 2018). Therefore, we used photography, positive posterior cross bite from plaster cast and positive temporomandibular disorder in a cohort of 10-30 year old patients based on their initial dental record in this study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Dental positions are modified, as well as muscles and soft tissue, in order to prevent extractions (FRÄNKEL et al, 1969;CHADWICK et al, 2001;SCANAVINI et al, 2012, PARANHOS et al, 2013.…”
Section: Introductionmentioning
confidence: 99%